DERMATOLOGICAL MANIFESTATIONS OF DENGUE FEVER - Mahboob, Atiya; Iqbal, Zafar; Javed, Rabail; Taj, Azeem; Munir, Asma; Saleemi, Munir Akhtar; Yaqub, Faryal (Journal of Ayub Medical College Abbottabad, 2012)
Background: Each year dengue related infections are rising in tropical countries. There is not enough data available on dermatological manifestations of dengue fever. This study was conducted to investigate prevalence and type of dermatological manifestations of dengue fever (DF), Dngue Haemorrhagic Fever (DHF), and Dengue Shock Syndrome (DSS). Methods: A Prospective study was contacted in Department of Medicine, Shaikh Zayed Hospital, Lahore, from 3rd Oct to 20th Nov 2010. Specific serological tests for DF were done in all 60 patients admitted with suspected diagnosis of DF, DHF or DSS. Forty-eight confirmed cases were evaluated for age, gender, mucocutaneous features and outcome of the disease. Results: Forty-eight out of 60 patients had positive serology for dengue fever. Male to female ratio was 1.09:1. Their ages ranged 5-68 years with a mean of 31.5±15.2. DF, DHF and DSS were found in 71%, 19% and 10% respectively. Common dermatological presentations were oral mucous membrane congestion (66.67%), generalised morbiliform rash (64.58%) and eye congestion (64.58%). Purpuric spots along with mucous membrane congestion, generalised morbiliform rash and eyes congestion was observed in 20.83%, 12.5% and 6.25% patients respectively. All except one patient improved clinically. One patient died of respiratory distress and haemorrhage on second day of admission. Conclusion: Dermatological features are significantly noticeable in dengue fever patients. These may help us in early diagnosis and better management of patients. Keywords: Dengue fever, Dengue haemorrhagic fever, Dengue shock syndrome, Dermatological features